To Review on Aromatherapy and Herbs List Use in Aromatherapy - Parihar, Shweta; C, Chattarpal; Sharma, Devender (Asian Journal of Pharmaceutical Research and Development, 2022)
Aromatherapy is the use of essential oils derived from herbs, flowers, and other plants for therapeutic purposes. Essential oils can enter the body through the skin or through the olfactory system. Aromatherapy is delivered in a variety of ways, including diffusers, baths, massage, and compresses. Aromatherapy is the use of essential oils derived from herbs, flowers, and other plants for therapeutic purposes. The goal of this overview was to give a summary of systematic reviews that evaluated the efficacy of aromatherapy. This overview aims to summarise and critically assess all systematic evaluations on aromatherapy as a treatment for any health problem. Our ultimate goal is to provide clearer recommendations to clinicians on the efficacy of this method.